OPINIONS ABOUT ALLOTTING STRAINS ON THE LAYERS OF A LAMINATED MONOLITH COMPOSITE - RADU IATAN; FLORESCU PAVEL; GEORGIANA LUMINIŢA ENĂCHESCU; GHEORGHIȚA TOMESCU (Journal of Engineering Studies and Research)
A previous paper stated the method of determination of the neutral surface of a composite monolithic, laminate composite, organizing some of the component layers, go to the method of distribution of tasks developed in one given case. This regard illustrates several possible options of which results can enable a proper assessment of the maximum strains and alignment layers, ensuring a maximum lifting capacity. The study can be developed to optimize the organization of layers, depending on the practical purpose of using the composite structure (mechanical, thermal and / or sound).